Instrumentation, cooling, and initial testing of a large, conduction-cooled, react-and-wind MgB2 coil segment for MRI applications. (17th July 2018) - Zhang, D; Kovacs, C; Rochester, J; Majoros, M; Wan, F; Sumption, M D; Collings, E W; Rindfleisch, M; Panik, D; Doll, D; Avonce, R; Tomsic, M; et al.
Abstract: A react-and-wind MgB2 coil segment for a conduction-cooled magnetic resonance imaging (MRI) machine has been fabricated and tested. The coil was developed as part of a collaborative effort on a conduction-cooled, MgB2 -based, whole-body MRI image guided radiation therapy device. This study focuses on the fabrication, winding, instrumentation, cooling, and initial critical current ( I c ) testing of this near-full-size MgB2 segment coil. The coil was 0.9 m in diameter; the winding pack, 44.0 mm wide × 50.6 mm high, used 1.7 km of an 18 filament MRI-style conductor with Nb chemical barriers, Cu interfilamentary matrices, and an outer monel sheath. The conductor was insulated and reacted before winding onto a stainless steel former. The coil was instrumented with Cernox and E-type thermocouple temperature sensors, strain sensors, and voltage taps. The conduction-cooled coil was mounted in a cryostat capable of accepting coils of up to 0.9 m in diameter and 0.5 m in height. Critical current measurements were performed as a function of temperature during a controlled heating of the coil. The operational target was I  = 200 A at 13 K. The full magnet was designed to produce 0.75 T in the imaging area (at I  = 200 A), with a maximum field of 1.93 T in the winding. The single segment coil measured here exceeded this operation specification, with an I c of 280 A at 15 K and a maximum field 1.93 T in the winding. The coil was modeled using a finite element method, and a load line plot showed that 100% of short sample was reached at 21.5 K and above. These measurements demonstrate the viability of conduction-cooled MgB2 background coils as replacements for liquid helium cooled NbTi background coils in future MRI devices.